Enhancing concrete sustainability: use of ground glass pozzolans as a supplementary cementitious material in low carbon concrete. - Prasad Rangaraju (Revista ALCONPAT)
This review summarizes the availability and processing of glass waste and highlights its impact on the fresh and hardened properties of concrete. Concrete industry is increasingly seeking sustainable supplementary cementitious materials (SCMs) to partially replace Portland cement, as traditional SCMs like fly ash and slag face declining availability. SCMs enhance concrete’s mechanical and durability properties while reducing its carbon footprint. Processed glass waste has emerged as a promising alternative pozzolan, supported by extensive research and field applications. In response, ASTM developed C1866/C1866M-20, a standard specification for ground glass pozzolan in concrete. The potential of ground-glass pozzolans as viable supplementary cementitious materials (SCMs) for producing low-carbon concrete is also discussed.